Directions of the First Year Students’ Adaptation to the Conditions of Study at Higher Educaional Establishment - Oksana Humenyk (Pedagogical Discourse, 2012)
Information about psychological and pedagogical peculiarities of first-year students’ adaptation to the educational process of higher school is studied in the article. The information can be useful for high school teachers